Co‐existence of Distinct Supramolecular Assemblies in Solution and in the Solid State. Issue 10 (22nd December 2016) - Reddy, G. N. Manjunatha; Huqi, Aida; Iuga, Dinu; Sakurai, Satoshi; Marsh, Andrew; Davis, Jeffery T.; Masiero, Stefano; Brown, Steven P.
Abstract: The formation of distinct supramolecular assemblies, including a metastable species, is revealed for a lipophilic guanosine (G) derivative in solution and in the solid state. Structurally different G‐quartet‐based assemblies are formed in chloroform depending on the nature of the cation, anion and the salt concentration, as characterized by circular dichroism and time course diffusion‐ordered NMR spectroscopy data. Intriguingly, even the presence of potassium ions that stabilize G‐quartets in chloroform was insufficient to exclusively retain such assemblies in the solid state, leading to the formation of mixed quartet and ribbon‐like assemblies as revealed by fast magic‐angle spinning (MAS) NMR spectroscopy. Distinct N−H⋅⋅⋅N and N−H⋅⋅⋅O intermolecular hydrogen bonding interactions drive quartet and ribbon‐like self‐assembly resulting in markedly different 2D 1 H solid‐state NMR spectra, thus facilitating a direct identification of mixed assemblies. A dissolution NMR experiment confirmed that the quartet and ribbon interconversion is reversible–further demonstrating the changes that occur in the self‐assembly process of a lipophilic nucleoside upon a solid‐state to solution‐state transition and vice versa. A systematic study for complexation with different cations (K +, Sr 2+ ) and anions (picrate, ethanoate and iodide) emphasizes that the existence of a stable solution or solid‐state structure may not reflect the stability of the same supramolecular entity in another phase. Abstract : Ribbon or quartet or both? The co‐existence of distinct supramolecular assemblies formed by a lipophilic guanosine derivative is characterized in solution and in the solid state, through a combined solution and solid‐state NMR (20 T, 75 kHz magic angle spinning) spectroscopy approach. The reversibility of the self‐assembly phenomena is demonstrated.